The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.oraloncology.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Double positivity for HPV-DNA/p16ink4a is the biomarker with strongest diagnostic accuracy and prognostic value for human papillomavirus related oropharyngeal cancer patients

Abstract: Double positivity for HPV-DNA/p16, a test that can be easily implemented in the clinical practice, has optimal diagnostic accuracy and prognostic value. Our results have strong clinical implications for patients' classification and handling and also suggest that not all the HPV-related OPC behave similarly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 28 publications
5
78
1
Order By: Relevance
“…This is one of the few studies that evaluated multiple biomarkers and their associated outcomes from a large population‐based cohort of OpSCC patients . Similarly, our results supported the prognostic significance of the presence of HR‐HPV in these patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is one of the few studies that evaluated multiple biomarkers and their associated outcomes from a large population‐based cohort of OpSCC patients . Similarly, our results supported the prognostic significance of the presence of HR‐HPV in these patients.…”
Section: Discussionsupporting
confidence: 82%
“…However, in the other large‐scale study (n = 788), the authors found that HPV‐positive/p16 overexpression, not other tested markers, was a better outcome predictor. The different results may be due to different frequency of HPV positive in different geographic locations (10% in the Spain cohort vs 78% in our study) and different methods in HPV detection used (PCR‐based in Mena et al and in situ‐based in current study). We have also identified smoking history, tumor staging, and treatment as independent factors that can predict the outcomes.…”
Section: Discussioncontrasting
confidence: 55%
“…Of the 17 institution‐matched OPSCC studies, the pooled proportion that was HPV‐positive was 0.60 (95%CI: 0.45–0.74), albeit with high heterogeneity of results across studies ( p heterogeneity <0.0001, I 2 = 0.99). On average, the HPV prevalence of OPSCC was 10% higher than SCCUPHN (95%CI: 1–19%; p < 0.0001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Detection of HPV-DNA, in combination with p16 and/or HPV mRNA evaluation, represents one of the most reliable diagnostic approaches for the identification of HPV-driven OPSCCs. 15 Staining for p16 alone, without confirmation of HPV status with an HPV-specific test, will negatively affect the clinical management of p16 þ /HPV À patients. 16 Both direct and indirect methods for the detection of HPV-DNA on FFPE tissues have been used.…”
mentioning
confidence: 99%